Analysis of the Influence of Cultural Commodification, Digital Tourism, and Virtual Exoticism on Public Perceptions of Cultural Tourism in East Java - Hendratri, Bhaswarendra Guntur; Muhtadi, Muhamad Ammar; Arini, Rani Eka (Westscience Press, 2025)
This study examines the influence of cultural commodification, digital tourism, and virtual exoticism on public perceptions of cultural tourism in East Java. Using a quantitative research design, data were obtained from 115 respondents through a structured questionnaire utilizing a five-point Likert scale. Statistical analysis was conducted using SPSS version 25, including validity, reliability, classical assumption tests, and multiple linear regression. The findings reveal that all three independent variables—cultural commodification, digital tourism, and virtual exoticism—have a positive and significant influence on public perception. Among them, digital tourism has the strongest impact, indicating the vital role of digital media in shaping audience engagement and cultural understanding. The results also show that these three variables collectively explain 69.7% of the variation in public perception of cultural tourism. This demonstrates that digital representations and market-driven adaptations increasingly mediate modern cultural tourism. The study highlights the importance of balancing cultural authenticity and digital innovation to foster sustainable tourism development in East Java. It provides both theoretical insights and practical guidance for policymakers, cultural managers, and local communities in preserving cultural identity while leveraging digital opportunities.